Communicative participation outcomes in individuals with Parkinson's disease receiving standard care speech‐language therapy services in community settings. - Baylor, Carolyn; Linna Jin, Jingyu; Mach, Helen; Britton, Deanna (International Journal of Language & Communication Disorders (John Wiley & Sons, Inc.), 2024)
Background: The Communicative Participation Item Bank (CPIB) is a patient‐reported outcome measure (PROM) designed to measure the extent of interference, or difficulty, experienced by adults with communication disorders participating in their day‐to‐day communication activities. To date, there is limited evidence regarding sensitivity of the CPIB for capturing change with intervention in people with Parkinson's disease (PwPD). Aims: The purpose of this study was to examine the following measurement properties of the CPIB in PwPD who received community‐based, standard care, speech‐language therapy focusing on motor speech concerns: Change over time between treatment and observation groups, comparison to patient‐defined ideal and satisfactory targets, comparison of static short form to computerised adaptive testing (CAT), comparison of self to proxy‐rated scores, and comparison to other common PROMs. Methods and Procedures: Forty‐six PwPD (20 treatment/26 observation) completed data collection upon enrolment (pre‐treatment) and 6 months later. In addition to the CPIB, PROMs included the Voice Handicap Index 10‐item short form (VHI‐10), PROMIS Global Health‐Related Quality of Life, Levels of Speech Usage, self‐rated speech severity, and Patient Health Questionnaire‐9 (PHQ‐9). Participants also engaged in qualitative interviews. Forty‐four family members completed proxy CPIB ratings. Outcomes and Results: There were no significant differences between treatment and observation groups on the CPIB pre‐treatment, but there were significant differences post‐treatment. The differences appeared to be largely due to significant gains in the treatment group. No participants reached their ideal CPIB target, and few reached their satisfactory target. Static CPIB short form and CAT scores were not significantly different, with an average of five CAT items administered per participant. Overall group similarities between patient and proxy scores may have obscured wide variability across individual patient‐proxy pairs. Associations between CPIB and VHI‐10, health‐related quality of life, self‐reported speech severity, and depression ranged from weak to moderate. Conclusions and Implications: The CPIB appears to be sensitive to capturing change with intervention, and similar results are obtained with the static short form and CAT formats. One clinical caution is that even with gains observed in the treatment group, no participants obtained their ideal communicative participation goals, and few obtained a satisfactory level of communicative participation. Thus, while current interventions are beneficial, they may not meet the full range of clients' communication needs. While responding to the CPIB through a proxy rater may be feasible, caution is warranted due to concerns about maintaining the autonomy of PwPD. What this paper adds: What is already known on this subject: The communication disorders associated with Parkinson's disease (PD) can have a negative impact on quality of life and life participation as measured by patient (or person)‐reported outcome measures (PROMs). The Communicative Participation Item Bank (CPIB) is one PROM available to use with adults with communication disorders. However, little is known about whether the CPIB captures changes in communicative participation as a result of standard care treatment for people with Parkinson's disease (PwPD). Use of computerised adaptive testing (CAT), proxy report and comparison to targeted participation outcomes have not been explored. What this study adds to existing knowledge: As a result of this study, we know that the CPIB captured differences between treatment and observation groups after community‐based, standard care speech therapy intervention focusing on motor speech production in PwPD. Static short form and CAT scores did not differ significantly, so the CAT option provides better efficiency requiring, on average, five items to administer compared to the 10‐item short form. Proxy and PwPD scores did not differ as a group, but wide variability was noted. What are the potential or actual clinical implications of this work?: The CPIB may be a clinically sensitive instrument for capturing changes in communicative participation after treatment. No participants met their ideal CPIB target, and few reached their satisfactory target, suggesting that while current interventions contribute to gains in communicative participation, there are still unmet needs that may call for support and interventions addressing the more complex array of factors affecting communicative participation outcomes for PwPD.